Reference genes for gene expression analysis in proliferating and differentiating human keratinocytes. Issue 4 (April 2015) - Lanzafame, Manuela; Botta, Elena; Teson, Massimo; Fortugno, Paola; Zambruno, Giovanna; Stefanini, Miria; Orioli, Donata
Abstract: Abnormalities in keratinocyte growth and differentiation have a pathogenic significance in many skin disorders and result in gene expression alterations detectable by quantitative real‐time RT‐PCR (qRT‐PCR). Relative quantification based on endogenous control (EC) genes is the commonly adopted approach, and the use of multiple reference genes from independent pathways is considered a best practice guideline, unless fully validated EC genes are available. The literature on optimal reference genes during in vitro calcium‐induced differentiation of normal human epidermal keratinocytes (NHEK) is inconsistent. In many studies, the expression of target genes is compared to that of housekeeping genes whose expression, however, significantly varies during keratinocyte differentiation. Here, we report the results of our investigations on the expression stability of 15 candidate EC genes, including those commonly used as reference in expression analysis by qRT‐PCR, during NHEK calcium‐induced differentiation. We demonstrate that YWHAZ and UBC are extremely stable genes, and therefore, they represent optimal EC genes for expression studies in proliferating and calcium‐induced differentiating NHEK. Furthermore, we demonstrate that YWHAZ/14‐3‐3‐zeta is a suitable reference for quantitative comparison of both transcript and protein levels.